Protein engineering: the potential of remote mutations. (22nd March 2019) - Wilding, Matthew; Hong, Nansook; Spence, Matthew; Buckle, Ashley M.; Jackson, Colin J.
Abstract : Engineered proteins, especially enzymes, are now commonly used in many industries owing to their catalytic power, specific binding of ligands, and properties as materials and food additives. As the number of potential uses for engineered proteins has increased, the interest in engineering or designing proteins to have greater stability, activity and specificity has increased in turn. With any rational engineering or design pursuit, the success of these endeavours relies on our fundamental understanding of the systems themselves; in the case of proteins, their structure–dynamics–function relationships. Proteins are most commonly rationally engineered by targeting the residues that we understand to be functionally important, such as enzyme active sites or ligand-binding sites. This means that the majority of the protein, i.e. regions remote from the active- or ligand-binding site, is often ignored. However, there is a growing body of literature that reports on, and rationalises, the successful engineering of proteins at remote sites. This minireview will discuss the current state of the art in protein engineering, with a particular focus on engineering regions that are remote from active- or ligand-binding sites. As the use of protein technologies expands, exploiting the potential improvements made possible through modifying remote regions will become vital if we are to realise the full potential of protein engineering and design.